2013
DOI: 10.1111/cfs.12057
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational pathways leading to foster care placement of foster care alumni's children

Abstract: This study examined a path model that postulated intergenerational relationships between biological parent psychosocial functioning and foster care alumni mental health, economic status, and social support; and from these to the likelihood of children of foster care alumni being placed in foster care. The sample included 742 adults who spent time in foster care as children with a private foster care agency and who reported having at least one biological child. A full pathway was found between poorer father’s f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…This figure increased to 17% by age 23/24 (Courtney et al 2009), and to 19% by age 25/26 (Courtney et al 2011). Similarly, findings from a large cohort study in the US (742 care leaver parents aged between 20 and 49) revealed that 9% reported having a child in foster care, compared to a foster care rate of 1.1% in the general population (Foster Jackson, Beadnell and Pecora 2015). Broadhurst and Mason (2013) have also raised concern about the over-representation of care-experienced parents in their English sample of women who have been subject to repeat care proceedings.…”
Section: Introductionmentioning
confidence: 99%
“…This figure increased to 17% by age 23/24 (Courtney et al 2009), and to 19% by age 25/26 (Courtney et al 2011). Similarly, findings from a large cohort study in the US (742 care leaver parents aged between 20 and 49) revealed that 9% reported having a child in foster care, compared to a foster care rate of 1.1% in the general population (Foster Jackson, Beadnell and Pecora 2015). Broadhurst and Mason (2013) have also raised concern about the over-representation of care-experienced parents in their English sample of women who have been subject to repeat care proceedings.…”
Section: Introductionmentioning
confidence: 99%
“…Living in poverty makes it highly likely that engagement in formal mental health services and opportunities to build coping skills such as the arts, sports, or other recreation would be luxuries that few alumni could afford. In addition, adult alumni of foster care are often parents (Jackson Foster, Beadnell, & Pecora, 2015). Therefore, the negative impacts of poverty are likely to affect their ability to adequately care for their own or their family’s basic needs and health-related services.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other evidence tends to focus on a particular outcome or findings are drawn from a specific sample. For example, a US cohort study involving 742 care-experienced parents (aged between 20 and 49) 9% reported having a child in foster care, compared to a 1.1% rate for the general population (Foster Jackson, Beadnell and Pecora 2015). Similarly, freedom of information requests issued by the Centre for Social Justice (2015: 72) concluded "at least one in 10 young care leavers aged 16-21 … hav[ing] had a child taken into care in the last year".…”
Section: Background and Rationalementioning
confidence: 99%